ARM Assembly Language with Hardware Experiments - Elahi, Ata (Springer, 2015)
ARM is one of the leading suppliers of microprocessors for the entire world. ARM has designed and developed a CPU that partner companies can manufacture and add more peripherals to the processor. An ARM processor has a wide range of applica tion in today’s technology, such as mobile phones, tablets, televisions, and auto mobiles. Learning the ARM instruction set and ARM assembly programming is an essential tool in the development of low-level applications for the ARM processor. Engineers will benefit significantly from the understanding of computer architec ture and assembly language, especially if they are working in an industry where performance is crucial or hardware is being developed...